(untitled) (Journal of Engineering, 2011)
In this current work, Purpose; to clearly the fundamental idea for constructing a design and investigation of spur gear made of composite material its comes from the combination of (high speeds, low noise, oil-les running, light weight, high strength, and more load capability) encountered in modern engineering applications of the gear drives, when the usual metallic gear cannot too overwhelming these combinations. An analyzing of stresses and deformation under static and dynamic loading for spur gear tooth by finite element method with isoparametric eight-nodded in total of 200 brick element with 340 nods in three degree of freedom per node was selected for this analysis. This is responsible for the catastropic failure studying of spur gear made of composite material. Also obtain the natural frequencies and the mode shape of the composite tooth under (concentrated and or moving on surface profile) load of one half sinusoidal type impulse for two types of composite materials (Glasses/Epoxy & Graphite/Epoxy) and they are compared with the mild steel gear values. The appearances that improve the successfully of composite gear in the weight, stiffness, load capability, and dynamic behavior respect to the mild steel, which is found that composite materials may also be thought of as a material for power transmission gearing, from a stress point of view.